2022
DOI: 10.1021/acs.est.1c07801
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study for Antimony Adsorption and Precipitation on Hematite Facets

Abstract: Heterogeneous reactions at the mineral–water interface are of paramount importance in controlling the transport of contaminants. Herein, antimony (Sb) adsorption and subsequent precipitation on Fe2O3 facets were explored to understand its partitioning mechanisms by multiple complementary techniques. Our extended X-ray absorption fine structure spectroscopy and density functional theory results provided a consensus on the local coordination environment of Sb­(III) and Sb­(V) on Fe2O3 facets. We observed that Sb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 38 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Therefore, iron minerals could generate a considerable amount of ROS in the long term and play a role in accelerating biogeochemical processes as well as pollutant dynamics. For instance, previous studies on interactions between pollutants and iron minerals typically focus on interfacial hydrolysis, adsorption, and immobilization processes; this study suggests that pollutant transformation processes should be considered with ROS photochemically produced on the iron mineral surface. In other words, the iron mineral surface may act as a hotspot for pollutant transformation.…”
Section: Environmental Implicationsmentioning
confidence: 95%
“…Therefore, iron minerals could generate a considerable amount of ROS in the long term and play a role in accelerating biogeochemical processes as well as pollutant dynamics. For instance, previous studies on interactions between pollutants and iron minerals typically focus on interfacial hydrolysis, adsorption, and immobilization processes; this study suggests that pollutant transformation processes should be considered with ROS photochemically produced on the iron mineral surface. In other words, the iron mineral surface may act as a hotspot for pollutant transformation.…”
Section: Environmental Implicationsmentioning
confidence: 95%
“…Similar bonding modes were found in Cr­(VI), As­(III/V), and Sb­(III/V) adsorption, which was attributed to semblable R O–O in these anions (2.82–3.09 Å, Figure S7, Table S7). ,, These oxyanions readily form the 1 V complex when R Fe–Fe is significantly larger than R O–O (Figure a). When R Fe–Fe is comparable with R O–O , 2 C complex forms upon adsorption (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Based on fitting EXAFS data, an Sb−Sb backscattering path was observed when Sb(V) exceeded a monolayer surface coverage, which was interpreted as an indication for a polynuclear surface precipitate. In a more recent study, Yan et al 31 examined surface adsorption and subsequent precipitation of Sb on hematite (Fe 2 O 3 ) facets. They observed that the initial Sb adsorption and the subsequent precipitation were associated with Sb loadings and hematite facets, and an alteration in the surface binding mode of Sb from edge-sharing to corner-sharing may facilitate the formation of NaSb(OH) 6 precipitates.…”
Section: Aqueous Dynamics and Sorption Of As(v) And Sb(v)mentioning
confidence: 99%